Exploring Multicultural Education through a Research-Based Learning: A Case Study of Sanggar Anak Alam - Wardani, Ella Kusuma; Ambarwati, Unik; Fathurrohman; Lailelleru, David; Retnasari, Lisa (International Journal of Learning Reformation in Elementary Education, 2025)
The diverse and multicultural educational dynamics of Indonesian society demand an inclusive model that is responsive to cultural diversity. The national curriculum often fails to accommodate multicultural values. This study explores the development of multicultural learning through a research-based learning cycle method at Sanggar Anak Alam (SALAM), a culture-based non-formal schooling. A qualitative case study design was used, and data were collected through interviews, observation, and document analysis involving 35 participants. Thematic analysis and triangulation with Atlas.ti revealed three main findings: 1) inclusive understanding strengthens student multicultural awareness; 2) the learning cycle method proved effective in instilling multicultural values; and 3) close collaboration between facilitator parents and schools was key to driving innovation in learning practices. The model developed in this study contributes significantly as a prototype for enriching culturally responsive curriculum that can be adapted into formal education systems to build students' multicultural competence, critical thinking, and empathy.